Enhancing Security in Cross-Border Payments: A Cyber Threat Modeling Approach - Amiruddin, Amiruddin; Briliyant, Obrina Candra; Windarta, Susila; Setiadji, Muhammad Yusuf Bambang; Priambodo, Dimas Febriyan (JOIV : International Journal on Informatics Visualization, 2025)
Cross-border payment (CBP) systems are critical to the global economy but are increasingly susceptible to cyber threats due to their complex structures and diverse transaction models. This paper analyzes cyber vulnerabilities across four CBP models: correspondent banking (SWIFT), infrastructure (ApplePay), closed-loop (PayPal), and peer-to-peer (Ripple). It employs the STRIDE methodology and adapts the cyber threat modeling framework proposed by Khalil et al. Key objectives include identifying vulnerabilities, assessing the impact of threats, and proposing mitigation strategies. The corresponding banking model shows the highest threat impact due to extensive transaction elements crossing trust boundaries. In contrast, the closed-loop model demonstrates lower vulnerability because of fewer components outside its trust boundary. Peer-to-peer and infrastructure models present moderate risk levels influenced by blockchain transparency and infrastructure dependencies. Critical threats identified include abuse of authority, malware, and script injection, which can result in significant losses, such as financial theft, service outages, and data breaches. Results indicate that interactions between processes across trust boundaries exacerbate cyber risks. Strategic recommendations include reducing system complexity, reinforcing security protocols at trust boundaries, and integrating advanced threat detection mechanisms. The study highlights these vulnerabilities and risks and underscores the need for robust cybersecurity measures to protect CBP systems. This research contributes to the existing knowledge by providing a detailed threat assessment and practical insights for improving CBP security. Future studies should explore alternative modeling methods, update security contexts to reflect real-world scenarios, and analyze the impact of open banking technologies.